2021
DOI: 10.1101/2021.04.07.437873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking of Anopheles stephensi in Ethiopia using mitochondrial DNA reveals pattern of spread

Abstract: The recent detection of the South Asian malaria vector Anopheles stephensi in the Horn of Africa (HOA) raises concerns about the impact of this mosquito on malaria transmission in the region. The mode and history of introduction is important for predicting the likelihood of continued introduction and future spread. Analysis of An. stephensi genetic diversity and population structure can provide insight into the history of the mosquito in the HOA. We investigated genetic diversity of An. stephensi in eastern E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…We also noted that Lawyacado has the highest number of observed haplotypes ( n = 3). This follows the trend observed in Ethiopia, where the highest diversity was observed in the northern sites and those most proximal to the eastern border [ 29 ]. Preliminary evidence of differences in the level of diversity and genetic differentiation between sites should be followed up with population genomic analysis.…”
Section: Resultssupporting
confidence: 84%
“…We also noted that Lawyacado has the highest number of observed haplotypes ( n = 3). This follows the trend observed in Ethiopia, where the highest diversity was observed in the northern sites and those most proximal to the eastern border [ 29 ]. Preliminary evidence of differences in the level of diversity and genetic differentiation between sites should be followed up with population genomic analysis.…”
Section: Resultssupporting
confidence: 84%
“…Work by Carter et al has shown that An. stephensi populations in Ethiopia in the north and central regions can be differentiated genetically, potentially indicating that these populations are a result of more than one introduction into Ethiopia from South Asia, further emphasizing the potential role of anthropogenic movement on the introduction of the species 17 .…”
Section: Discussionmentioning
confidence: 99%
“…stephensi populations now established in these countries, there is a new threat to malaria control on the African continent. Population genetic analyses suggest the potential source of introduction is South Asia 17 .…”
mentioning
confidence: 99%
“…stephensi populations in Ethiopia in the north and central regions can be differentiated genetically, potentially indicating that these populations are a result of more than one introduction into Ethiopia from South Asia, further emphasizing the potential role of anthropogenic movement on the introduction of the species (Carter et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…stephensi populations now established in these countries, there is a new threat to malaria control on the African continent. Population genetic analyses suggest the potential source of introduction is South Asia (pre-print by Carter et al 2021).…”
Section: Introductionmentioning
confidence: 99%